(untitled) (MAUSAM, 1984)
The dry farming tract in India, where annual rainfall varies from 40 to 100 cm, comprises of 105 districts in nine States. In this tract rainfall is the limiting factor for successful raising of crops, In order to stabilising the crop at certain level even in a low rainfall year, it is essential to know the frequency of drought years so that agricultural planning is drawn up on a rational scientific basis, For the purpose, amongst other things, it is necessary to know the minimum week by week rainfall at different probability levels. In this paper the lowest amount of rainfall at different probability levels (10 to 90% ) has been computed by fitting incomplete gamma distribution probability model to weekly rainfall totals of 87 stations in the dry farming tract during the Indian monsoon season. The same amount of rainfall behaves differently, in terms of water availability to plaits depending upon atmospheric demand. Moisture Availability Index (MAI) which is defined as ratio of probabilistic rainfall of a week to potential evapotranspiration has been computed, Crop requires various amount of water at its different growing phases and least one third of potential demand is necessary even in the early stage. Moisture availability index at 50% level has been used to map out drought prone areas. The period when MAI >= 0.3 has been taken as the crop growing period, The mid-season water stress period, i.e., when MAI >= 0.3 has been found out from 50% probability level and this period has been used to map out drought prone area both in time and space, Severity of drought has been classified by the number of water stress periods -as well as their durations. Drought proneness has also been discussed at other probability levels whenever necessary. Applying the present criteria, drought prone area both in time and space in the dry farming tract has been demarcated. A drought prone area is found extending from Aurangabad in Maharashtra to Bangalore in Karnataka. Occurrence of drought is frequent in Gujarat and eastern Rajasthan.